PENJADWALAN PROYEK EFO (EXPORTABLE FINE ORE) PADA INDUSTRI PERTAMBANGAN - Anita, Anita (Jurnal Cakrawala Ilmiah, 2023)
Project scheduling is the activity of determining the timeframe for project activities to be completed, raw materials, labor and time needed by each activity. PT. Ifishdeco Tbk. is a private company engaged in the mining of raw nickel ore, which includes exploration, development and sale of nickel ore. This study aims to study the scheduling of EFO (Exportable Fine Ore) projects. There is a difference in the project scheduling between plan and realization, namely for the plan it is estimated to be completed in 30 days but in the implementation of the project realization it is completed within 79 days, so the project experiences a time difference between plan and realization which is 49 days. Delays in working on projects can be due to delays in material delivery and weather factors